KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA PADA PEMBELAJARAN MATEMATIKA KELAS IV - Sulistiani, Sanita; Marzuki, Marzuki; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is aims ability to describe ability of students in working on math word problem at 4th grade in SDN 27 Pontianak Utara. Overall the ability of students to solve story problems is still lacking value average  = (55,60). The method used is descriptive with the survai research form.Who were selected to be interviewed were 6 people. Data collection tools in the form of written tests in the form of essays with a total of 4 questions.Based on the results of the study of students' ability to understand the problem of high and medium group story problems can write what is known and what is asked correctly and completely.  Low groups can only write what is known.  The ability of students to make a plan to solve the problem of the middle and high mathematics groups can write the formula in solving the problem correctly and completely, the low math group writes the formula but it is less precise and incomplete.  The ability to implement a mathematical group problem solving plan can write the completion process thoroughly and the results are correct, the math group is successful in writing the completion process without the strand and the results are correct, the math group is low.  The ability to look back on the results obtained by the medium and high mathematics groups checks again the answers obtained and concludes the answers.  Low math groups do not check the results obtained but write conclusions of incomplete answersKeywords: Learning Marhematics,  Math Word Problem, Students Ability